St. Thomas - French Village, Charlotte Amalie - Tichnor Brothers... (Wikimedia Commons, 1952)
Notice image issue de Wikimedia Commons. Titre: St. Thomas - French Village, Charlotte Amalie. Photomechanical print (postcard): halftone, colored
Licence Public domain via Wikimedia Commons
Keywords: carte postale; image; Patrimoine; architecture; Histoire Locale